Validity and reliability of the questionnaire that evaluates factors associated with perceived environmental behavior and perceived ecological purchasing behavior in Peruvian consumers. Issue 3 (14th June 2019) - Lopez-Odar, Dennis; Alvarez-Risco, Aldo; Vara-Horna, Aristides; Chafloque-Cespedes, Raquel; Sekar, M. Chandra
Abstract : Purpose: The purpose of this study is to determine the metric properties of a questionnaire that evaluates environmental and ecological purchasing behavior, environmental personal norms, environmental identity and environmental social influence. Design/methodology/approach: The validity and reliability of the scales of the questionnaires were determined in a sample of 2445 consumers from Lima (Peru), selected through non-probabilistic sampling by quotas and by factorial analysis based on Classical Theory of Tests (CTT) and Structural Equations of Variance with Partial Least Squares (SEM-PLS). Findings: The results support the construct and discriminant validity of the instrument, as well as the internal consistency of all the subscales (Cronbach's alpha between 0.662 and 0.8887 – composite reliability between 0.815 and 0.917). Research limitations/implications: Customers evaluated were only from Lima city. It would be important to evaluate, in future research, customers from other cities in Peru. Practical implications: Although a large number of instruments have been designed, not all are based on integral theoretical models, and their metric properties were determined with methodological criteria that restrict their applicability. Therefore, there is a need to have valid and reliable instruments for the identification of environmental behavior and ecological purchasing. Social implications: This "new questionnaire" integrates the exploration of environmental behavior and ecological purchasing, along with the measurement of personal environmental norms, environmental identity and the social influence received from peers and teachers, to provide a comprehensive picture of the consumer behavior. Originality/value: This research constitutes a theoretical and practical contribution to the understanding and evaluation of ecological behavior and some of its associated factors. Its main contribution is the adaptation of this instrument to the Peruvian context and the validation of an instrument that evaluates environmental and ecological purchasing behavior, personal environmental standards, environmental identity and environmental social influence.